Terminologi Gambus dalam Spektrum Musik di Indonesia - Ricky Irawan (Journal of Music Science, Technology, and Industry, 2020)
This Article aims to review the expansion of the meaning of gambus in three categories. It is, firstly, the gambus as a musical instrument; secondly, gambus as a music performance format; and thirdly, stringed as a musical style. This categorization helps to understand the context in which the term gambus is used. Thus, the discussion about gambus can be understood more clearly. It was found that, initially, the term gambus is used to refer to a stringed musical instrument from the Middle East that came together with trading activities and the spread of Islam in Southeast Asia. But in its development, gambus is also used to refer to a format of musical performances such as orkes gambus, gambus Melayu, gambus tunggal and others. Later, gambus was used also to refer to musical styles associated with Islamic musical arts such as gambus dzikir, gambus sholawat, gambus qasidah. Seeing the various uses, it is difficult to interpret it only as the name of a musical instrument, but must also accommodate the expansion of its meaning at this time.